2017
DOI: 10.2147/jpr.s122918
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural analgesia reduces myocardial injury in ischemic patients undergoing major abdominal cancer surgery

Abstract: Background and objectivesMajor abdominal cancer surgeries are associated with significant perioperative mortality and morbidity due to myocardial ischemia and infarction. This study examined the effect of perioperative patient controlled epidural analgesia (PCEA) on occurrence of ischemic cardiac injury in ischemic patients undergoing major abdominal cancer surgery.Patients and methodsOne hundred and twenty patients (American Society of Anesthesiologists grade II and III) of either sex were scheduled for elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A meta-analysis also showed that use of epidural analgesia reduced pulmonary complications after abdominal and thoracic surgery, probably due to earlier mobilization, reduced opioid consumption, and improved cough [ 20 ]. In a recent study, use of perioperative thoracic epidural analgesia reduced the occurrence of major adverse cardiac events (including deep venous thromboembolism) after major abdominal cancer surgery in patients suffering from coronary artery disease [ 21 ]. For the first time, our results showed that combined use of epidural anesthesia/analgesia was associated with decreased risk of postoperative complications in patients undergoing open abdominal surgery for pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis also showed that use of epidural analgesia reduced pulmonary complications after abdominal and thoracic surgery, probably due to earlier mobilization, reduced opioid consumption, and improved cough [ 20 ]. In a recent study, use of perioperative thoracic epidural analgesia reduced the occurrence of major adverse cardiac events (including deep venous thromboembolism) after major abdominal cancer surgery in patients suffering from coronary artery disease [ 21 ]. For the first time, our results showed that combined use of epidural anesthesia/analgesia was associated with decreased risk of postoperative complications in patients undergoing open abdominal surgery for pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the type of surgery, thoracic and upper abdominal surgeries appear to be associated with a higher risk of arrhythmia than surgeries at other sites. 18 , 19 For a better surgical view and approach, robotic gastrectomy is usually performed under the head-up position. The head-up position might have been a contributing factor to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study findings above are in line witha study done by the [8] which found out that 77.4% of respondents knew of traditional home remedies and potentially used them during first aid management of burns [17][18][19][20][21][22] The study findings above are still consistent with a study done in Kwa-Zulu Natal by [17], which revealed that 59.2 % used substances like eggs, butter, and soap during first aid management of burns. This could be because community members lack of information about the negative effects resulting in use of traditional home remedies during the first aid management of burns in children under five years [23][24][25][26][27].…”
Section: Findings On Practices Of Community Members Towards First Aid...mentioning
confidence: 99%